PENGARUH PENGETAHUAN AKUNTANSI, MANAJEMEN SUMBER DAYA MANUSIA DAN KEPRIBADIAN WIRAUSAHA TERHADAP KINERJA USAHA DI USAHA MIKRO KECIL DAN MENENGAH (UMKM) ROTAN DI DESA TRANGSAN SUKOHARJO - Lisa Ayu Ramadhani; Rukmini Rukmini; Hadi Samanto (Jurnal Akuntansi dan Pajak, 2024)
The aim of this research is to determine the significant influence of Accounting Knowledge, Human Resource Management, Entrepreneurial Personality on the Performance of rattan MSME Businesses in Trangsan Village. The type of data used is primary data using the Slovin formula obtained from 58 sample respondents. The data collection techniques used are, Observation, Interview, Questionnaire. The data analysis methods used are descriptive analysis tests, validity tests and reliability tests. The classical assumption tests used are the normality test, multicollinearity test, and heteroscedasticity test. Hypothesis testing uses the t test using SPSS 23. The results of the study show that accounting knowledge, human resource management, entrepreneurial personality have a significant effect on business performance in the rattan UMKM of Trangsan Village